2012
DOI: 10.1111/j.1365-2486.2011.02616.x
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from soils: synthesis and analysis of a large UK data set

Abstract: The NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 54 publications
3
115
1
Order By: Relevance
“…The correlation between the depth of the water table and CH 4 fluxes accords with field experiments [Heikkinen et al, 2002;Nykänen et al, 1998], suggesting that an inverse relationship exists between water table position and CH 4 fluxes (deeper water tables lead to smaller emissions). In addition, the heterogeneity of soil properties is also an important control on the variations of CH 4 emissions [Levy et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation between the depth of the water table and CH 4 fluxes accords with field experiments [Heikkinen et al, 2002;Nykänen et al, 1998], suggesting that an inverse relationship exists between water table position and CH 4 fluxes (deeper water tables lead to smaller emissions). In addition, the heterogeneity of soil properties is also an important control on the variations of CH 4 emissions [Levy et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…[8] To begin, we collected direct CH 4 flux chamber measurements of wetland ecosystems in the northern high latitudes from peer-reviewed literature [e.g., Glagolev et al, 2011;Levy et al, 2011]. Our data contain CH 4 flux chamber measurements from 34 sites, covering a range of wetland types under various field conditions (Table 1 and Figure 1).…”
Section: Data Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, low water levels and oxygen availability are also key drivers of nitrous oxide (N 2 O) production in organic soils (Regina et al, 1996), which increases the relevance of organic soils for climate change mitigation policy. During anaerobic conditions when water levels are at or above the land surface, substantial methane (CH 4 ) emissions can occur (Levy et al, 2012).…”
Section: Bechtold Et Al: Large-scale Regionalization Of Water Tabmentioning
confidence: 99%
“…Freibauer and Kaltschmitt (2003) reported that the fluxes of N to the atmosphere and to ground water by leaching (Hack-ten Broeke et al 1999) are greater from the intensively managed grasslands than from croplands due to higher nitrate input. Lee et al (2006) and Abdalla et al (2014) observed negative CH 4 fluxes from cropland; however, fluxes from organic soils, which are typically poorly drained in their natural state (not included in this study), could be high (Levy et al 2012). However, the estimate of an annual net GHG balance of 0.34 Mt CO 2 e y -1 assumes stability of existing land uses, and any recent historic land use change is a source of uncertainty in the result, e.g.…”
Section: Effects Of Climate Change On Ghg and Soc Fluxes And Net Primmentioning
confidence: 93%